-(-2)^3 + 3(-2)^2 - (-2) + 4 = -8 + 12 + 2 + 4 = 10
0 + 0- 0 = 4
-(3)^3 + 3(3)^2 - 3 + 4 = -27 + 27 - 3 + 4 = 1
The 1st one should be -(-2)^3 = - (-8) = 8, not -8
2007-05-25 14:14:02
·
answer #1
·
answered by richardwptljc 6
·
0⤊
0⤋
f(x) = –x3 + 3x2 – x + 4
f(-2)=8+12+2+4=26
f(0)=4
f(3)=-27+27-3+4=1 answer
2007-05-25 14:16:41
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
f(x) = - x³ + 3x² - x + 4
f(- 2) = 8 + 12 + 2 + 4 = 26
f(0) = 4
f(3) = - 27 + 27 - 3 + 4 = 1
2007-05-27 07:38:29
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
I'm assuming in your equation that x3 means x^3 and 3x2 is 3x^2 then:
f(-2) = 26
f(0) = 4
f(3) = 1
2007-05-25 14:18:42
·
answer #4
·
answered by Scooter 1
·
0⤊
0⤋
f(-2)= -(-2)^3 + 3(-2)^2 - (-2) + 4
= 8 + 12 + 2 +4 = 26
f(0)= 4
f(3)= -(3)^3 +3(3)^2 - (3) +4
= -27 +27 - 3 +4 = 1
2007-05-25 14:22:36
·
answer #5
·
answered by Queen JJ 2
·
0⤊
0⤋
f(-2) for every x that you see in f(x) you will replace it with a -2
f(-2)=-(-2)^3 + 3(-2)^2 - (-2) + 4
f(-2)=-(-8)+3(4)+2+4
f(-2)=8+12+2+4=26
and you do the same with f(0)
f(0)=-(0)^3 + 3(0)^2 - 0 + 4
f(0)=0+0-0+4=4
f(3)=-(3)^3 + 3(3)^2 - 3 + 4
f(3)=-(27) + 27 -3 +4
f(3)=-3+4=1
2007-05-25 14:43:08
·
answer #6
·
answered by wouldn't-u-like-to-know ;] 3
·
0⤊
0⤋
f(-2) = 26
f( 0) = 4
f( 3 ) = 1
2007-05-25 14:28:01
·
answer #7
·
answered by bigennice5 1
·
0⤊
0⤋